2015
DOI: 10.4236/pp.2015.612060
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcerogenic Effect of Brazilian Propolis Formulation in Mice

Abstract: Propolis is a natural resin used around the world to treatment of several diseases. We evaluated the effect of Brazilian propolis (P1) in guinea pig isolated trachea in vitro contracted with histamine, in paw oedema induced by histamine in mice and anti-ulcerogenic effect of propolis formulation in mice. We used a P1 extract from South of Brazil to produce a formulation containing sodium bicarbonate and propolis dry extract (2%). In the guinea pig trachea Brazilian propolis extract (10 µg/mL) produced a non-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Recent research conducted by Paulino et al (2015) compared the anti-inflammatory effects of sodium diclofenac and propolis. Both compounds demonstrated anti-inflammatory effects; however, sodium diclofenac can cause ulcerogenic disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research conducted by Paulino et al (2015) compared the anti-inflammatory effects of sodium diclofenac and propolis. Both compounds demonstrated anti-inflammatory effects; however, sodium diclofenac can cause ulcerogenic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Both compounds demonstrated anti-inflammatory effects; however, sodium diclofenac can cause ulcerogenic disease. However, additional research has indicated that propolis may inhibit the formation of ulcers caused by sodium diclofenac (Paulino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another experimental study indicated the antihistaminergic, antiinflammatory, anti-H. pylori activities and antiacid, of Propolis that could be used for the treatment of gastric ulceration [57]. Artepillin C and another phenolic mixtures available in Brazilian Propolis clears free radicals and decrease the oxidative stress relevant to inflammation [57]. Treatment with Propolis attenuated the levels of LPS (lipopolysaccharide) and down-regulated the TLR4 pathway and expressions of inflammatory markers in muscle of experimental mice, and improved serum triacylglycerols and glucose levels, also decreased inflammatory cytokines and endotoxemia by inhibiting dysbiosis in mice experimented with a high-fat diet [58].…”
Section: Propolis and Its Effect On Gastrointestinal Diseasementioning
confidence: 99%
“…This study demonstrated transformation of the pear-shaped cell and decrease beating frequency of flagellar in the trophozoites [ 56 ]. Another experimental study indicated the antihistaminergic, antiinflammatory, anti- H. pylori activities and antiacid, of Propolis that could be used for the treatment of gastric ulceration [ 57 ]. Artepillin C and another phenolic mixtures available in Brazilian Propolis clears free radicals and decrease the oxidative stress relevant to inflammation [ 57 ].…”
Section: Role Of Propolis In Inflammationmentioning
confidence: 99%
“…Moreover, antimicrobial besides antiulcer and immunomodulatory properties could be detected [14]. Propolis was promisingly proposed to manage giardiasis with minimal side effects [15].…”
Section: Introductionmentioning
confidence: 99%